2022
DOI: 10.1002/cai2.23
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of immune checkpoint inhibitors for extensive‐stage small‐cell lung cancer

Abstract: Small‐cell lung cancer (SCLC) accounts for 15%–20% of primary lung cancers, and it is characterized by low differentiation, rapid proliferation, and early metastasis. At least two‐thirds of SCLC patients present with the extensive stage (ES) at the time of initial clinical diagnosis. Over the last 2 decades, platinum‐based combination chemotherapy has remained the standard first‐line treatment for SCLC. With the introduction of the immunotherapy era, immunotherapy plus chemotherapy has replaced conventional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Immunotherapy modalities also play an important role in the survival benefit of patients. Basic studies have shown that chemotherapy is able to induce immunogenic cell death and promote tumor antigen release 22 , 23 . Bevacizumab promotes DC maturation and promotes more efficient T cell priming and activation, while it induces normalization of tumor vasculature, thereby promoting effector lymphocyte infiltration into tumor tissue 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy modalities also play an important role in the survival benefit of patients. Basic studies have shown that chemotherapy is able to induce immunogenic cell death and promote tumor antigen release 22 , 23 . Bevacizumab promotes DC maturation and promotes more efficient T cell priming and activation, while it induces normalization of tumor vasculature, thereby promoting effector lymphocyte infiltration into tumor tissue 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of mostly retrospective studies, all <IIB NSCLC, showed a 1-year overall survival (OS) of 83 to 98% and 5-year OS between 22.5 and 55.7%. 43 The choice of RFA versus SABR in early-stage NSCLC remains controversial. A retrospective study of 6,195 stage 1a nonsurgical NSCLC patients found no significant difference between RFA and SABR; however, a meta-analysis including 105 studies demonstrated similar short-term survivals but better long-term survivals for SABR.…”
Section: Lung Ablationmentioning
confidence: 99%
“…Among these therapies, immunotherapy has become the mainstream of modern cancer treatment ( 45 ) by manipulating the self-immune system to recognize and attack cancer cells and has achieved unprecedented success in clinical trials. Especially for lung cancer, as the most common cancer worldwide, the prognosis of advanced NSCLC ( 46 ) and extensive‐stage small‐cell lung cancer (SCLC) ( 47 ) was significantly improved with the administration of immunotherapy. Up to now, two PD1 inhibitors Nivolumab and Pembrolizumab and one PD-L1 inhibitor Atezolizumab have been approved as standard treatment options for NSCLC patients ( 48 ).…”
Section: Introductionmentioning
confidence: 99%